2006
DOI: 10.1051/0004-6361:20042619
|View full text |Cite
|
Sign up to set email alerts
|

The solar cycle as a forced and damped harmonic oscillator: long-term variations of the amplitudes, frequencies and phases

Abstract: We model solar activity cycle as a forced and damped harmonic oscillator consisting of two parts, sinusoidal and transient. The amplitudes, frequencies, phases and decay factors of such a harmonic oscillator are determined by fitting the equation of the sinusoidal and transient parts to the sunspot data for the years 1755-1996 (cycles 1-22) with the results: (i) there is a long-term decreasing trend in the phase, while the amplitude and the frequency (or period of ∼11 yr) of the sinusoidal part remain constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Damping would cause the system to relax to the driving period 2p=x 0 if there were no stochastic disturbances to this equilibrium. Hiremath (2006) fitted the parameters of the forced and damped oscillator model to each observed solar cycle individually; then in a later work (Hiremath 2008) he applied linear regression to the resulting series to provide a forecast (see Sect. 4.1 above).…”
Section: The Sun As An Oscillatormentioning
confidence: 99%
“…Damping would cause the system to relax to the driving period 2p=x 0 if there were no stochastic disturbances to this equilibrium. Hiremath (2006) fitted the parameters of the forced and damped oscillator model to each observed solar cycle individually; then in a later work (Hiremath 2008) he applied linear regression to the resulting series to provide a forecast (see Sect. 4.1 above).…”
Section: The Sun As An Oscillatormentioning
confidence: 99%
“…They used a wavelet analysis on geomagnetic index (aa) and the yearly averaged Wolf sunspot numbers since 1844 and found that, a non-linear coupling function between sunspot maxima and aa minima modulations. Hiremath (2006) modeled the solar cycle as a forced and damped harmonic oscillator and from all the 22 cycles , long-term amplitudes, frequencies, phases and decay factor are obtained. Using these physical parameters of the previous 22 solar cycles and by an autoregressive model, they predict the amplitude and period of the future 15 solar cycles.…”
Section: Sunspot Cycle Prediction Techniques -A Reviewmentioning
confidence: 99%
“…Those parameters could be estimated by subjecting to a non-linear least square fit by the Levenberg-Marquardt method (Hiremath, 2006;Press et al, 1992). Frequency and damping rate in Eq.…”
Section: Second-pass Segmentation Algorithm and Model Fittingmentioning
confidence: 99%